2009
DOI: 10.1073/pnas.0902723106
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human Rad51 protein filament from molecular modeling and site-specific linear dichroism spectroscopy

Abstract: To get mechanistic insight into the DNA strand-exchange reaction of homologous recombination, we solved a filament structure of a human Rad51 protein, combining molecular modeling with experimental data. We build our structure on reported structures for central and N-terminal parts of pure (uncomplexed) Rad51 protein by aid of linear dichroism spectroscopy, providing angular orientations of substituted tyrosine residues of Rad51-dsDNA filaments in solution. The structure, validated by comparison with an electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
78
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 39 publications
4
78
0
1
Order By: Relevance
“…In both new studies (7,8), the ATP binding site is found not in the interior of individual subunits (as suggested by earlier structural studies of the relatively inactive form of RecA) but at the subunit-subunit interface. This arrangement in active, DNA-bound recombinase filaments had been predicted by the EM image reconstructions of Egelman and colleagues (10).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…In both new studies (7,8), the ATP binding site is found not in the interior of individual subunits (as suggested by earlier structural studies of the relatively inactive form of RecA) but at the subunit-subunit interface. This arrangement in active, DNA-bound recombinase filaments had been predicted by the EM image reconstructions of Egelman and colleagues (10).…”
mentioning
confidence: 59%
“…In archaeal RadA and eukaryotic Rad51 proteins, this residue is highly conserved as Tyr or Phe. In both new studies (7,8), DNA binding loops in the protein interiors, inferred but largely unresolved in earlier structures, are found adjacent to the DNA, allowing the role of key amino acid residues to be assigned. The new picture of recombinase-DNA interactions, coupled to published kinetic studies (e.g., ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RecA-DNA 복합체의 X 선 결정구조 해석에 서 RecA는 L1 루프 및 L2 루프라고 불리는 2 개의 루프를 통 해 DNA와 결합하는 것이 밝혀졌다 (Chen et al 2008). 이 DNA 결합 루프는 RAD51에서도 보존되어 있다 (Matsuo et al, 2006;Reymer et al 2009 (Kurumizaka et al 1996. 이 C 말단 도메인은 필라 멘트의 외측에 결합한 DNA를 내측의 DNA 결합 루프로 이 끄는 게이트웨이로 간주되고 있다 (Kurumizaka et al 1996.…”
Section: 상동 재조합효소 Rad51unclassified
“…This recombinase-ssDNA nucleoprotein filament, commonly referred to as the presynaptic filament, undergoes a conformational change upon ATP-binding such that it becomes activated for homologous DNA pairing and strand exchange (12,13). Furthermore, the presynaptic filament possesses a second binding site that can accommodate a duplex DNA molecule (14,15). As such, the presynaptic filament provides the catalytic scaffold to sample the incoming duplex DNA and form first an unstable paranemic joint with the ssDNA, which can mature into a stable plectonemic joint in which the recombining DNA strands are linked topologically (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%